Kotlin Design Patterns and Best Practices - Second Edition : Build Scalable Applications Using Traditional, Reactive, and Concurrent Design Patterns in Kotlin. - Soshin, Alexey (Packt Publishing, Limited, 2022)
Improve the scalability and maintainability of your applications by implementing a variety of design patterns using Kotlin Key Features Understand traditional and modern design patterns to improve the design of your application Combine the benefits of object-oriented, functional, reactive, and concurrent programming Choose the best microservices architecture and frameworks for your web application Book Description Design patterns are well-known solutions to common architectural problems as they allow you to solve many problems efficiently and create a shared vocabulary between developers. This book shows you how easy it can be to implement traditional design patterns in the modern multi-paradigm Kotlin programming language, and takes you through the new patterns and paradigms that have emerged. This second edition is updated to cover the changes introduced from Kotlin 1.2 up to 1.5 and focuses more on the idiomatic usage of coroutines, which have become a stable language feature. You'll begin by learning about the practical aspects of smarter coding in Kotlin, and will understand basic Kotlin syntax and the impact of design patterns on your code. The book also provides an in-depth explanation of the classical design patterns, such as Creational, Structural, and Behavioral families, before moving on to functional programming. You'll go through reactive and concurrent patterns, and finally, get to grips with coroutines and structured concurrency to write performant, extensible, and maintainable code. By the end of this Kotlin book, you'll have explored the latest trends in architecture and design patterns for microservices, as well as understanding the tradeoffs when choosing between different architectures. What you will learn Implement all the classical design patterns using the Kotlin programming language Apply reactive and concurrent design patterns to make your application more scalable Discover best practices in Kotlin and explore its new features Understand the key principles of functional programming and learn how they apply to Kotlin Find out how to write idiomatic Kotlin code and learn which patterns to avoid Harness the power of Kotlin to design concurrent and reliable systems with ease Create an effective microservice with Kotlin and the Ktor framework Who this book is for This book is for developers looking to apply design patterns they've learned from other languages in Kotlin to build reliable, scalable, and maintainable applications. Prior programming knowledge is necessary to get started with this book. Experience in Java or design patterns is helpful, but not mandatory.